Agrotóxicos em vinho: avaliação do método QuEChERS e da microextração líquido-líquido dispersiva na determinação multirresíduo por UHPLC-MS/MS - Bernardi, Gabrieli (2017)
The widespread use of pesticides in agriculture has brought many benefits such as, increasing quantity and quality of crops grown. However, there is a concern regarding to the presence of pesticide residues in the consumed manufactured food products. Due to this, it is necessary to monitor pesticides in these products in order to verify compliance with maximum residue limits. Wine is a beverage obtained from grape must, but the grapes grown for this purpose are susceptible to pest attack and the occurrence of fungal diseases. Since the wine quality is related to the grapes quality, its production is dependent on the use of pesticides. Currently, the most useful way to determine the pesticides residues in food is the application of multiresidue methods that allow the determination of several compounds from different classes in a single analytical process. Based on that, the aim of this work was to evaluate two multiresidue methods for the extraction of pesticides in wine, one of them being based on the QuEChERS method and the dispersive liquid-liquid microextraction with the use of demulsifying solvent (SD-DLLME). Parameters that affect the extraction efficiency of both methods were studied and after established the best extraction conditions the methods were validated. The use of ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) allowed to perform the determination with high selectivity and sensitivity. For the QuEChERS method, 97 compounds were validated and the limit of quantification of the method (LOQ) ranged from 10 to 20 μg L-1. For SD-DLLME, 74 compounds were validated and LOQ were between 0.1 and 0.2 μg L-1. Among the compounds not validated by SD-DLLME are compounds with polar characteristics, not suitable for this technique. Pesticides residues of different classes were found in the samples the concentrations of 0.8 to 55.3 μg L-1. In view of the results obtained, the use of SD-DLLME proved to be a viable alternative to the QuEChERS method for the multiresidue determination of pesticides in wine.